1991
DOI: 10.1111/j.1365-2990.1991.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of rubella and measles viruses in primary rat neural cell cultures: relevance to a postulated triggering mechanism for multiple sclerosis

Abstract: Rubella virus multiplied to low titre and produced a partial cytopathic effect in rat glial cell cultures. Anti-galactocerebroside staining showed that this cytopathic effect involved the disintegration of oligodendrocytes. A similar effect was produced following infection of myelinating neural cell cultures with rubella virus, but virus multiplication could not be detected in pure neuron cultures. Measles virus was found to multiply and produce a cytopathic effect in primary cultures of both neurons and glial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
5
16
1
Order By: Relevance
“…In in vitro cultures infected with the Edmonston vaccine strain, virus antigen was detected in oligodendrocytes but not in neurones until 6 dpi, reflecting the ex vivo findings. This contrasts with an earlier report of infection of purified rat neuronal and glial cultures with the Edmonston MV strain where the virus was detected earlier in neurones than glial cells [36]. In another study a comparison of infection in primary hippocampal neuronal cultures from CD46 transgenic and nontransgenic embryonic mice with the Edmonston vaccine strain found that no infection was detected in the latter when examined up to 6 days [12].…”
Section: Discussioncontrasting
confidence: 58%
“…In in vitro cultures infected with the Edmonston vaccine strain, virus antigen was detected in oligodendrocytes but not in neurones until 6 dpi, reflecting the ex vivo findings. This contrasts with an earlier report of infection of purified rat neuronal and glial cultures with the Edmonston MV strain where the virus was detected earlier in neurones than glial cells [36]. In another study a comparison of infection in primary hippocampal neuronal cultures from CD46 transgenic and nontransgenic embryonic mice with the Edmonston vaccine strain found that no infection was detected in the latter when examined up to 6 days [12].…”
Section: Discussioncontrasting
confidence: 58%
“…HB has been previously described to have homologous amino acid stretches with human MBP (Wucherpfenning and Strominger, 1995). Atkins et al (1991) have shown a sequence similarity between the amino‐terminus of human PLP and RV envelope E 1 protein. In this work, we analyzed structural glycoprotein E 2 of RV that was found to induce high specific antibody titers in MS patients (Nath and Wolinsky, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…We searched for a potential viral candidate that would exhibit sufficient molecular mimicry with MOG to induce demyelinating antibodies. We focused on HB and RV, which have long been implicated in MS (Atkins et al, 1991). RV is a togavirus with a molecular biology similar to that of SFV.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these investigations there are very few studies that have utilized either primary cells or oligodendrocyte cell lines to study MV infection in this important cell type. In one previous report, Atkins et al (1991) reported that a nonrodent-adapted strain of Edmonston strain of MV multiplied and produced a cytopathic effect in primary cultures of rat oligodendrocytes (Atkins et al, 1991). Viral infection in that study was only monitored by cytopathic effects and no viral immunocytochemistry or ultrastructural investigations were undertaken.…”
Section: Introductionmentioning
confidence: 98%